Das Vorabentscheidungsverfahren in Deutschland und in Polen - Thiele, Alexander; Łukańko, Bernard (Mohr Siebeck, 2023)
What is the significance of the preliminary ruling procedure before the ECJ? How does an ECJ ruling affect the national legal system? What is the practice of complying with preliminary rulings in Germany and Poland in individual areas of law? This anthology, the result of a research project of Polish and German lawyers, attempts to answer these questions.
PublicationDate: 20230616
Keywords: Europäischer Gerichtshof -- Europäisches Prozessrecht -- Europäisches Verfahrensrecht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Arbeits- und Sozialrecht -- Europarecht -- Ausländisches Recht, Rechtsvergleichung